Favorable Changes in Biomarkers of Potential Harm to Reduce the Adverse Health Effects of Smoking in Smokers Switching to the Menthol Tobacco Heating System 2.2 for 3 Months (Part 2). Issue 4 (24th May 2019) - Haziza, Christelle; de La Bourdonnaye, Guillaume; Donelli, Andrea; Skiada, Dimitra; Poux, Valerie; Weitkunat, Rolf; Baker, Gizelle; Picavet, Patrick; Lüdicke, Frank
Abstract: Introduction: Tobacco Heating System (THS) 2.2, a candidate modified-risk tobacco product, aims at offering an alternative to cigarettes for smokers while substantially reducing the exposure to harmful and potentially harmful constituents found in cigarette smoke. Methods: One hundred and sixty healthy adult US smokers participated in this randomized, three-arm parallel group, controlled clinical study. Subjects were randomized in a 2:1:1 ratio to menthol Tobacco Heating System 2.2 (mTHS), menthol cigarette, or smoking abstinence for 5 days in confinement and 86 subsequent ambulatory days. Endpoints included biomarkers of exposure to harmful and potentially harmful constituents (reported in our co-publication, Part 1) and biomarkers of potential harm (BOPH). Results: Compliance (protocol and allocated product exposure) was 51% and 18% in the mTHS and smoking abstinence arms, respectively, on day 90. Nonetheless, favorable changes in BOPHs of lipid metabolism (total cholesterol and high- and low-density cholesterol), endothelial dysfunction (soluble intercellular adhesion molecule-1), oxidative stress (8-epi-prostaglandin F2α ), and cardiovascular risk factors (eg, high-sensitivity C-reactive protein) were observed in the mTHS group. Favorable effects in other BOPHs, including ones related to platelet activation (11-dehydrothromboxane B2) and metabolic syndrome (glucose), were more pronounced in normal weight subjects. Conclusions: The results suggest that the reduced exposure demonstrated when switching to mTHS is associated with overall improvements in BOPHs, which are indicative of pathomechanistic pathways underlying the development of smoking-related diseases, with some stronger effects in normal weight subjects. Implications: Switching to mTHS was associated with favorable changes for some BOPHs indicative of biological pathway alterations (eg, oxidative stress and endothelial dysfunction). The results suggest that switching to mTHS has the potential to reduce the adverse health effects of smoking and ultimately the risk of smoking-related diseases. Switching to mTHS for 90 days led to reductions in a number of biomarkers of exposure in smokers, relative to those who continued smoking cigarettes, which were close to those observed when stopping smoking (reported in our co-publication, Part 1). Initial findings suggest reduced levels of 8-epi-prostaglandin F2α and intercellular adhesion molecule 1, when switching to mTHS for 90 days. These changes are comparable to what is observed upon smoking cessation. In normal weight subjects, additional favorable changes were seen in 11-dehydrothromboxane B2, fibrinogen, homocysteine, hs-CRP, percentage of predicted forced expiratory volume in 1 second, systolic blood pressure, diastolic blood pressure, glucose, high-density lipoprotein, apolipoprotein A1, and triglycerides. Trial registration: NCT01989156.